Development of Self-Change Classical Guidance Module to Reduce Studentâ€™s Stress Due to COVID-19 - Wahyudi, Hendro; Dharsana, I Ketut; Suranata, Kadek (Bisma The Journal of Counseling, 2021)
The COVID-19 pandemic is affecting to the learning process in school. As an effort to reduce the spread of virus, all of learning activity now conducted via online. Various obstacles arise during the online learning. This new condition increase the level of studentâ€™s stress and requires students ready to make self-change. This study is research and development that aims to develop and evaluate the classical guidance module as an instrument to help students make self-change in order to reduce their stress. The development procedure conducted by following 4D model (Thiagarajan, 1974). Five expert involved as judges to evaluate the content validity of module and 30 students were involved as subject on piloting study. Results of expert judgement were analyzed using formula Lawshe and show the module has a â€œvery specialâ€ content validity index ( CVI = 1). Results of piloting study show the module has â€œvery goodâ€ category in all aspect of evaluation. Based on the results, it show that the classical guidance module developed in this study feasible to use as an instrument to help students make self-change in order to reduce their stress levels due to COVID-19.